A study on the effectiveness of wells criteria for diagnosing deep vein thrombosis: a prospective observational study - Palanisamy, Dhanaraj; Omkumar, Akshay (International Surgery Journal, 2021)
Background: Wells score which takes into account various aspects in the history as well as various clinical signs which can help the clinician to arrive at a diagnosis of deep vein thrombosis (DVT). This helps to save time and money that is wasted in doing many unnecessary investigations. Aim of the study was to test the application of the Wells score in our clinical set up and to see how effectively we can diagnose DVT. Methods: This was a prospective diagnostic validation study of the wells rule for DVT in our setup, ultrasound (USG) being the gold standard comparison and will be conducted over a duration of 12 months. Wells score for each patient was calculated and the results were evaluated. Results: Among the 50 cases suspected DVT, the wells score was able to predict DVT in 46 of the cases thus proving to be a very efficient diagnostic indicator. The average wells score among the various cases was 4/8. Complications noted in the study group were 2 cases of cortical vein thrombosis in the post-partum period which fully recovered. Mortality rate in the study group was 4.3% in which a single case of diagnosed myocardial infarction died of heart failure. Conclusions: Wells score is indeed a very good predictive criteria for DVT and can be applied with ease as it required only clinical assessment and thus avoids unnecessary delays in waiting for scans thereby allowing us to start anticoagulants as early as possible.